ARTIFICIAL INTELLIGENCE-BASED CYBERPEDAGOGICAL MODEL OF DEVELOPING COMMUNICATIVE COMPETENCE OF PHILOSOPHY STUDENTS (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes the issues of introducing a cyberpedagogical approach using artificial intelligence (AI) technologies in teaching English to philology students in higher education institutions. The study suggests the need to move from traditional methods of developing communicative competence to a digital learning environment and a model for integrating AI tools (Large Language Models – LLM) into the educational process.
Keywords: cyberpedagogy, communicative competence, artificial intelligence, philological education, prompt engineering, adaptive teaching, linguistic didactics.